Understanding the Transfer of Concepts between the International and National Levels : Import or interpretation? - Kraus, Katrin [Verfasser] (My University, 2008)
"Against the background of the transformation of industrial labour societies into post-industrial service economies and the European integration, 'employability' has arisen as a major topic in education policy discourse at the European and national levels. Considering the transfer of ideas and policies as an active process tilts chapter analyses the understanding of employability in the European Union discourse and its transfer into the German context where the traditional concept of 'vocation' is still very strong and incorporated in the basic structures of society and economy. In order to analyse this process of concept transfer I introduce the 'earning schema' as a tertium comparationis. With this approach different understandings of 'employability' as well as different concepts like "employability" and "vocation" can be understood as historically developed forms how earning (in the sense of making a living) and the ability to earn are conceptualised The analysis shows that the recent discourse of employability in Germany is one interpretation of the European discourse. The concept of employability as it is understood in Germany very much reflects the traditional concept and the structure of this society, which supports the understanding of transfer as a two-sided process." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; T 2 Theoretische Ansätze; I 2.1 Deutschland; I 2.2 Europa; Beziehung Bildungssystem Beschäftigungssystem; Beschäftigungsfähigkeit; Begriff; Beruflichkeit; Wissenstransfer; Internationaler Vergleich; Bundesrepublik Deutschland; Europa